Implikasi Laju Inflasi Terhadap Gross Domestic Product (GDP) Berdasarkan Perspektif Ekonomi Islam - Muhammad Gunawan; Alfa Rohmatin (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This journal discusses the influence of the inflation rate on Gross Domestic Product (GDP) based on an Islamic Economics perspective. So it can be understood that the size of the inflation rate in a country will greatly influence the level of GDP. Where inflation has a simultaneous influence on GDP, and inflation has a partial negative impact on GDP. The writing of this journal uses a deductive qualitative approach (from general to specific), examining relevant general phenomena, then producing specific studies and conclusions on matters that are the object of research, using a normative juridical approach with literature study. A country's economic growth can be represented through an increase in the country's GDP, apart from income factors in terms of consumption, investment, government spending and net exports. GDP is greatly influenced by the inflation factor. Inflation in the view of Islamic economists is an economic indication that occurs at a macro level in almost every country related to the decline in the exchange rate of money for goods and services, whether it occurs naturally (natural inflation) or is caused by human error (Human Error Inflation). Inflation does not only occur naturally, it can be caused by the pull of Aggregate demand (Aggregate demand) or due to a decrease in Aggregate supply (Aggregate Supply), but also occurs due to human error in regulating state administration and law enforcement, giving rise to a country's economic interconnectedness. Maintaining the stability of a country's economy by controlling the rate of inflation is something very basic, where inflation significantly affects Gross Domestic Product. GDP is an important indicator of economic growth in measuring economic activity, especially the volume of production in a country in one year.